Uso de periódicos eletrônicos nas instituições do ensino superior e de pesquisa em Moçambique - Ranito Zambo Waete (2013)
The study took as reference the centrality and the impact of the Portals Electronics in Mozambique available for scientific research in the country. Therefore, we analyzed the degree of acceptance and use of Electronic Journals and Journals Portals of INASP, HINARI, AGORA and CAPES for teachers and researchers IESP in Mozambique. The methodology included a combination of qualitative and quantitative approaches. Also served up the documentary research, therefore, it was used in official documents and technicians collected from the bodies of the Government of the Mozambique, facing public policy information, science and technology. The research was composed of teachers, researchers of the IESP. Data collection was conducted through a questionnaire with open and closed questions. The study sample was characterized by convenience, being non-probabilistic and consisted of teachers and researchers from 20 IESP (total population) in Mozambique who are registered for access to Portals Electronics of INASP, HINARI, AGORA and CAPES. The results suggest that both teachers and researchers from IESP in Mozambique routinely use electronic journals in their teaching and research activities. However, the paper printing culture is still strongly present, and the preference for paper is the main reason for using only the printed journal. The same results showed that minority teachers and researchers, that despite the academic and scientific experience and time to practice, they are unaware of the existence of electronic journals and Portals Journals. Regarding the degree of satisfaction with the use of portals, they are reasonably satisfied, although they see language as a major barrier for accessing and using electronic journals available in Portals. They suggested that it was necessary wider dissemination of Portals Journals and more training courses for students, teachers and researchers. Furthermore, the study provided a broad overview how the different areas of knowledge in Mozambique make use of electronic journals.